Pengaruh e-WOM dan Kualitas Pelayanan Terhadap Minat Beli Ulang (UMKM Kuliner Sate Kambing Pak Pur Tawangmangu) - Erika Putri Mayangsari; Fransius Awaldo Damanik (STIE AUB Surakarta, 2025)
This study investigates the impact of electronic word of mouth (e-WOM) and service quality on repurchase intention among customers of Sate Kambing Pak Pur Tawangmangu. Using a purposive sampling technique, data were collected from 96 consumers and analyzed with SPSS Statistics 27. The findings demonstrate that both e-WOM and service quality exert positive and significant influences on repurchase intention, both partially and simultaneously. These results suggest that when consumers perceive positive online reviews and experience high-quality service, they are more likely to repurchase. The study implies that Sate Kambing Pak Pur should enhance its social media marketing strategies and consistently improve service quality to strengthen customer satisfaction, thereby fostering long-term loyalty and sustainable business growth.